Radiographic evaluation and comparison of triple pelvic osteotomy with and without additional ventral plate stabilization in forty dogs - part 1 - Fitch, R. B.; Kerwin, S.; Hosgood, G.; Rooney, M.; Pluhar, E.; Pelsue, D. (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
Triple pelvic osteotomies (IPO) were evaluated in 40 clinical cases. In 39 cases, these were young dogs with hip dysplasia; in one case, the TPO was used as a correction for a hip luxation. Unilateral TPOs were performed in twenty patients, twelve with traditional TPO (without additional ventral plate) and eight with additional ventral plate fixation. Bilateral TPOs were performed in twenty patients, thirteen with traditional TPO and seven with additional ventral plate. In traditional TPOs, evidence of implant failure occurred in 5 of 12 unilateral and 11 of 13 bilateral procedures. In TPOs with additional ventral plate fixation, minor screw loosening was detected in one of eight unilateral and zero of seven bilateral procedures. Statistically TPOs without additional ventral plate fixation had 9.2 times greater odds of screw loosening with significantly greater acetabular segment displacement (p < 0.01). Two traditional TPOs performed required additional surgery due to screw loosening. Other attempted additional stabilization techniques used with the TPO procedure included ilial body wiring, ischial body wiring, sacral screw purchase, and medial screw nuts, however these methods did not prevent loosening and migration. TPO with additional ventral plate fixation was highly effective at combating implant failure.
Keywords: Hip dysplasia; triple pelvic osteotomy; implant loosening